Application of strict liability principles in environmental dispute resolution - Muhammad Akib; Agus Triono; HS Tisnanta; Fathoni Hukum; Rodrikson Alpian Medlimo (Goodwood Publishing, 2023)
Purpose: The aim of this study is to analyze the factors causing the Strict Liability principle to not be implemented effectively and the efforts that can be made so that the Strict Liability principle can be implemented effectively. Research Methodology: This study employed a normative empirical method with a descriptive analysis approach. Secondary data is acquired through meticulous literature review and subjected to qualitative analysis. Rigorous literature selection ensures data validity. The outcomes of the analysis serve as the cornerstone for accurate conclusions within the research. Results: The results of the research show that the principle of Strict Liability cannot be implemented effectively because there are political deviations in the law of environmental dispute resolution after the enactment of the Job Creation Law and there are policy inconsistencies in resolving environmental disputes. Limitations: Environmental dispute resolution still uses the principle of liability based on fault, which requires proving elements of fault on the part of the defendant. In the context of resolving environmental disputes, there is still a basis for liability based on the principle of Strict Liability, which does not need to prove the defendant's fault if he has fulfilled the elements contained in Article 88 of Law Number 32 of 2009. Contribution: Efforts that can be made to implement the Strict Liability principle effectively are, first, reorienting policies and strategies for resolving environmental disputes. This can be realized by preventing, overcoming, and restoring pollution and damaging natural resources and the environment, as well as strengthening institutions and law enforcement in the field of natural resources and the environment. Second, there are legal political irregularities in resolving environmental disputes after the enactment of the Job Creation Law.